Das Hegemonieprojekt der ökologischen Modernisierung: Die Konflikte um Carbon Capture and Storage (CCS) in der internationalen Klimapolitik - Krüger, Timmo (transcript, 2015)
Ecological Modernization is considered a central principle of contemporary environmental politics. According to »sustainable development« and the »green economy«, the central demands of ecomodernism aim for progressive development, which is supposed to complement other components of sustainability. By way of Carbon Capture and Storage (CCS), Timmo Krüger enquires into the current dynamics in the hegemonic struggles in international climate politics. He shows that since CCS technologies are based on fossil fuels and centralized energy infrastructure, the question arises as to whether it can adequately contribute to a comprehensive transformation of societal structures given the nature of the existing ecological crisis.